Urban spaces, fragmented consciousness, and indecipherable meaning in Mrs Dalloway - Harrison, Andrew (Palgrave Macmillan, 2014)
This essay discusses the importance of urban spaces in Virginia Woolf's Mrs Dalloway, linking them to central themes in the novel (including the fragmented consciousness of the characters, and withheld - or only partially understood - meaning).